Determination of burst pressure of defective steel pipes using finite element analysis - Mohamad Zulfadli, Mohamad Rani (2012)
This thesis deals with assessment of defective API 5L X65 steel pipes which are widely used in product transportation in oil and gas industry. The objective of the thesis is to determine the burst pressure of defective API X65 steel pipes under the effect of gouge length for different pipe diameter. The thesis describes the finite element analysis techniques to predict the true fracture and identify the critical locations of the structures (pipe). One-quarter three-dimensional solid modelling of steel pipe was developed using the MSC Patran 2008r1 that act as a pre-processor. The finite element analysis was then performed using MSC Marc. The finite element model of the pipe was analyzed using the non-linear isotropic elasto-plastic material that obeys the incremental of plastic theory. The values of principal stresses and strains acted on the critical location of gouge defect had been obtained by MSC Patran as a post-processor. The values were used to determine the true fracture strain which is known to be exponentially dependent to the stress triaxiality. Finally, burst pressure was determined as the true fracture strain exceeds the value of equivalent strain at that instant point. Based on the results, it is observed that the analysis using SMCS model yields more conservative burst pressure prediction. The obtained results indicate that the shorter gouge length would gives higher burst pressure which means, higher pressure needed as the pipe to experience failure at the gouge defect area. Result shows that the burst pressure decreases with increment of pipe diameter. The results concluded that the shorter gouge length and smaller pipe diameter conditions give the highest pressure value of pipe burst. Therefore, the defect characteristic is the promising criteria to increase the fitness of service of the pipe.